A case non-traumatic neck pain managed with TECAR and conventional physiotherapy: a case report - Solanki, Pavan; Chitapure, Tajuddin; Kshirsagar, Ashwin (International Journal of Research in Medical Sciences, 2024)
Neck pain is most common musculoskeletal condition prevailing in India. About 70% have mechanical cause. Causing heavy burden on healthcare system and also on the economy. Trapezitis is an inflammation of the upper, middle, and lower trapezius muscle fibers it is the most common condition seen in Indian physiotherapy setups. The patient usually complains of pain and spam. Recent evidence is suggestive of effectiveness of conventional treatment approaches in treatment of trapezitis. This case is reporting 22-year male diagnosed with trapezitis is treated with TECAR and conventional physiotherapy. This study reports TECAR is with conventional physiotherapy is effective in treatment of pain, spasm and tenderness in patients and also shows improvement in cervical range of motion.